Effective Bulk Activation and Interphase Stabilization of Silicon Negative Electrode by Lithium Pre-Doping for Next-Generation Batteries. Issue 3 (18th December 2018) - Saito, Morihiro; Kato, Kiyomi; Ishii, Shunya; Yoshii, Kazuki; Shikano, Masahiro; Sakaebe, Hikari; Kiuchi, Hisao; Fukunaga, Toshiharu; Matsubara, Eiichiro
Abstract : To clarify the effects of Li pre-doping of a Si negative electrode for potential application in next-generation energy storage systems, such as Li–S and Li–O2 batteries, such electrodes were prepared by direct Li pre-doping using Li metal foil and by electrochemical pre-doping at 700 mA g −1 (Si) using a two-electrode cell. These were evaluated by comparing their charge/discharge properties, mainly by half-cell operation at a limited capacity of 2000 mAh g −1 (Si). Fluoroethylene carbonate (FEC) was added to form a stable solid electrolyte interphase film on the surface of the electrodes. The depth and homogeneity of Li pre-doping were improved by using the direct Li pre-doping method and by FEC addition, respectively. The rapid Li pre-doping of this method caused cracks and pulverization of the Si nanoparticles and promoted deep Li alloying by decreasing the Li + diffusion distance. The tough homogeneous solid electrolyte interphase film derived from FEC suppressed electrolyte decomposition and enabled a fast Li alloying/de-alloying reaction. Addition of 10 mass% FEC to the half-cell electrolyte repaired damage to the interphase film caused by the large volume change of Si nanoparticles and improved cyclability to exceed 230 cycles.